Investigation of one task of the potential theory - Aleksas Domarkas; Rimantas-Jonas Rakauskas; Svajonė Vošterienė (Lietuvos Matematikos Rinkinys)
Using computer algebra package Maple we compute aproximative analytical solution. For Clebsch–Gordan coefficients was used sparse matrix array.